2020
DOI: 10.1002/adhm.202000200
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Release of Neurotrophin‐3 and Chondroitinase ABC Enhances the Efficacy of Nerve Guidance Conduits

Abstract: Nerve guidance conduits (NGCs) have the potential to replace autografts in repairing peripheral nerve injuries, but their efficacy still needs to be improved. The efficacy of NGCs is augmented by neurotrophic factors that promote axon growth and by enzymes capable of degrading molecules that inhibit axon growth. In the current study, two types of NGCs loaded with factors (both neurotrophin‐3 and chondroitinase ABC) are constructed and their abilities to repair an 8 mm gap in the rat sciatic nerve are examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…7, the percentage of surviving RGCs on days 3, 7 and 14 were least in injury only group, and 37-40% survival rate seen on day 7, which is consistent with previous studies. 17,40 Intravitreal injection of TA and DBP displayed signicantly higher RGCs surviving rate on day 7 and 14, and showed better therapeutic effect compared to PLGA-FA, PLGA/ COL-TA and intraperitoneal FA. Interestingly, the survival rate of RGCs in FA-intraperitoneal treated animals declined to similar level to injury only group on day 14.…”
Section: Dbp Self-adheres To the Optical Tissues And Promotes Rgc Survival Post-tonmentioning
confidence: 98%
See 2 more Smart Citations
“…7, the percentage of surviving RGCs on days 3, 7 and 14 were least in injury only group, and 37-40% survival rate seen on day 7, which is consistent with previous studies. 17,40 Intravitreal injection of TA and DBP displayed signicantly higher RGCs surviving rate on day 7 and 14, and showed better therapeutic effect compared to PLGA-FA, PLGA/ COL-TA and intraperitoneal FA. Interestingly, the survival rate of RGCs in FA-intraperitoneal treated animals declined to similar level to injury only group on day 14.…”
Section: Dbp Self-adheres To the Optical Tissues And Promotes Rgc Survival Post-tonmentioning
confidence: 98%
“…This method can facilitate different drug encapsulation and transportation through a number of mechanisms. 17 Several bioactive agents, such as growth factors, 18 neuroprotective factors 6,19 and stem cells, 20 have shown encouraging therapeutic effects in animal models of TON but only a few have been translated clinically. Fasudil, a specic inhibitor of Rhoassociated protein kinase (ROCK), has been used to treat cerebral ischemia aer subarachnoid hemorrhage in many countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophin-3 (NT-3) can enhance Schwann cell migration and ensure their survival. Donsante et al (2020) showed that a continuous release of NT-3 from collagen-based electrospun fibers over a 2 week-period led to increased axon counts in the distal nerve. In a co-culture of DRG-derived neurons and then in dorsal root ganglia (DRG) explants NT-3 ensured ordinate and oriented axonal elongation ( Fornaro et al, 2020 ).…”
Section: Biological Functionalization Beyond the Hollow Tubementioning
confidence: 99%
“…Nowadays, stimuli-responsive devices are developed to fabricate smart devices, especially Near InfraRed (NIR), considering its deep penetration through tissues and acute control of temperature [ 23 , 24 ]. Xia et al [ [25] , [26] , [27] , [28] ] developed microparticles made of thermo-sensitive phase-change material (PCM) encapsulating photosensitive NIR dye, to achieve pulse drug release. As for NIR triggered system, the heater of high photothermal conversion efficiency and the valve of thermo sensitivity are determinant.…”
Section: Introductionmentioning
confidence: 99%